(untitled) (Journal of Partial Differential Equations, 2020)
In this paper, our main aim is to study the existence and uniqueness of the periodic solution of delayed Logistic equation and its asymptotic behavior. In case the coefficients are periodic, we give some sufficient conditions for the existence and uniqueness of periodic solution. Furthermore, we also study the effect of time-delay on the solution.